USE OF COMPLEMENTARY THERAPY TO IMPROVE BREAST MILK PRODUCTION FOR PUBLIC MOTHERS AT PMB SUBIATI SRAGEN - Merlinda Rachmawati; Aris Prastyoningsih; E Ernawati (Universitas Kusuma Husada Surakarta, 2023)
Mother's milk (ASI) is a safe and perfect source of nutrition and food for babies aged 0-6 months. It is hoped that adequate breastfeeding will have an impact on reducing infant morbidity and mortality rates. Based on a preliminary study of problems during breastfeeding such as swollen breasts, sore breasts and the use of formula milk which was carried out in October 2022 at PMB Subiati Srage, there were 22 postpartum mothers and 4 postpartum mothers. willing to be interviewed, the results were obtained, namely how to increase and facilitate breast milk, namely by consuming katuk leaf vegetables, spinach leaves, and drinking uyup-uyup herbal medicine. The aim of this research is to explore in depth the use of complementary therapies to smooth breast milk production for postpartum mothers at PMB Subiati Sragen. This type of research uses qualitative research with a phenomenological design. Data collection techniques were carried out using in-depth interviews. The results of this research are the use of vegetables, animal protein, herbs/herbal medicine in the process of facilitating breast milk production. The conclusion from the results of this study shows that complementary therapy is used by breastfeeding mothers as an option to increase breast milk production and facilitate breast milk production. study shows that complementary therapy is used by breastfeeding mothers as an option to increase breast milk production and facilitate breast milk production